[Haskell-beginners] Understanding the type signature of flip$id
Jeff Lasslett
jeff.lasslett at gmail.com
Thu Mar 3 00:07:43 CET 2011
Hi Christian,
As a beginner I think it's easier to read the intention of 'flip ($)'
rather than flip$id, where I found it
used to resolve command line arguments. Thanks for that.
Jeff
On 2 March 2011 18:51, Christian Maeder <Christian.Maeder at dfki.de> wrote:
> Maybe "flip ($)" is clearer? ($) is identity over function types.
>
> If you have the (first) argument you could use a section like "($ a)"
> and avoid flip.
>
> C.
>
> Am 02.03.2011 06:33, schrieb Jeff Lasslett:
>> Thanks Daniel,
>>
>> I think I follow what you've written.
>>
>> (b -> c) -> (b -> c) is the same as (b -> c) -> b > c
>>
>> and when that is flipped: b -> (b- > c) -> c
>>
>> Is that right?
>>
>> Thanks,
>> Jeff
>>
>>
>>
>> On 2 March 2011 11:23, Daniel Fischer <daniel.is.fischer at googlemail.com> wrote:
>>> On Wednesday 02 March 2011 00:43:23, Jeff Lasslett wrote:
>>>> I just don't understand how passing id to flip results in the
>>>> following type signature:
>>>>
>>>> Prelude> :t flip$id
>>>> flip$id :: b -> (b -> c) -> c
>>>>
>>>> I do understand what flip has done to map here:-
>>>>
>>>> Prelude> :t flip$map
>>>> flip$map :: [a] -> (a -> b) -> [b]
>>>>
>>>> map take a function and a list and produces a new list. If map is
>>>> passed to flip the result is a function that takes a list, then a
>>>> function and results in a new list.
>>>>
>>>> How do we go from flip having this signature:
>>>>
>>>> Prelude> :t flip
>>>> flip :: (a -> b -> c) -> b -> a -> c
>>>> Prelude>
>>>>
>>>> and id having
>>>>
>>>> Prelude> :t id
>>>> id :: a -> a
>>>> Prelude>
>>>>
>>>> to flip$id looking like flip$id :: b -> (b -> c) -> c ???
>>>>
>>>> Thanks,
>>>> Jeff
>>>
>>> The point is that the type of id has to be unified with the type of flip's
>>> (first) argument.
>>>
>>> flip :: (a -> b -> c) -> (b -> a -> c)
>>> id :: t -> t
>>>
>>> So we have to unify (a -> b -> c) and (t -> t). Fully parenthesized,
>>> a -> b -> c is a -> (b -> c). Now unification yields
>>>
>>> t = a
>>> -- id's arg must have the same type as the flip's argument's arg
>>>
>>> and
>>>
>>> t = (b -> c)
>>> -- id's result must have the same result as flip's argument's result
>>>
>>> From that follows a = (b -> c) and *id can be passed to flip only at a more
>>> restricted type than id's most general type, namely at the type
>>> id :: (b -> c) -> (b -> c)*
>>>
>>> So,
>>>
>>> flip (id :: (b -> c) -> b -> c) :: b -> (b -> c) -> c
>>>
>>
>
More information about the Beginners
mailing list